2004
DOI: 10.1111/j.1442-9993.2004.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fire on the Abundance of Xenarthrans in Mato Grosso, Brazil

Abstract: Fire is an important ecological factor in Cerrado vegetation of central Brazil, and in other savanna ecosystems. The effect of fire on the abundance of some Xenarthran mammal species Priodontes maximus Kerr, 1792 (giant armadillo), Euphractus sexcinctus Linnaeus, 1758 (yellow armadillo) and Myrmecophaga tridactyla Linnaeus, 1758 (giant anteater)) was studied at Reserva Xavante do Rio das Mortes, a 329 000 ha Xavante Indian reserve in the Cerrado of Mato Grosso, Brazil. Track counts were used to compare the abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…Our results are in accordance with most studies quantifying the effects of fire on tropical savanna biodiversity, which found little or no effect (van Wilgen et al, 2007;Frizzo et al, 2011), corroborating the adaptation of Cerrado biodiversity to fire, both among plants (e.g., Coutinho, 1982Coutinho, , 1990Simon and Pennington, 2012) or animals (e.g. Vieira and Marinho-Filho, 1998;Layme et al, 2004;Prada and Marinho-Filho, 2004). Recent studies, however, have shown fire influences other than changes in richness, such as body conditions of lizards, which depend on habitat preferences of different species (Costa et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are in accordance with most studies quantifying the effects of fire on tropical savanna biodiversity, which found little or no effect (van Wilgen et al, 2007;Frizzo et al, 2011), corroborating the adaptation of Cerrado biodiversity to fire, both among plants (e.g., Coutinho, 1982Coutinho, , 1990Simon and Pennington, 2012) or animals (e.g. Vieira and Marinho-Filho, 1998;Layme et al, 2004;Prada and Marinho-Filho, 2004). Recent studies, however, have shown fire influences other than changes in richness, such as body conditions of lizards, which depend on habitat preferences of different species (Costa et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Although changes in vegetation structure represent modifications in habitat for plants and animals, fire-driven changes in plant communities of tropical savannas due to fire are much more about structure than species composition or biodiversity (Higgins et al, 2007;van Wilgen et al, 2007;Lebbink et al, 2018), since fire does not eliminate typical savanna species. No biodiversity losses due to fire have been consistently observed in savannas for most animal groups, such as arthropods (but see Morais and Benson, 1988;Andersen and Müller, 2000;Maravalhas and Vasconcelos, 2014;Vasconcelos et al, 2017), birds (Cavalcanti and Alves, 1997;Corbett et al, 2003;Mills, 2004;Reis et al, 2016), mammals (Vieira, 1999;Prada and Marinho-Filho, 2004;Beale et al, 2018), reptiles (Griffiths and Christian, 1996;Corbett et al, 2003;Langford et al, 2007;Morais et al, 2011;Costa et al, 2013), and amphibians (Corbett et al, 2003;Langford et al, 2007;Morais et al, 2011). Despite the pattern of low impact on richness observed in most studies, however, there are some exceptions when fire effects are analyzed at a small scale, comparing different pieces of the vegetation mosaic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the immediate effect of a fire is a drastic change in the landscape, the mobility of medium and large mammals would allow most of them to escape and seek refuge in adjacent areas (Frizzo et al 2011). In these cases, gallery forests are important refuge areas for these species (Silveira et al 1999, Prada andMarinho-Filho 2004). Due to the rapid regrowth of the vegetation, soon after the fire, these highly resilient environments may be able to sustain populations of medium and large mammals again.…”
Section: Discussionmentioning
confidence: 99%
“…Focos de calor nas faixas de influência interna e externa de cada terra indígena. Entende-se que mais estudos devem ser conduzidos para continuar avaliando o efeito do fogo em terra indígena localizada na região do Rio das Mortes e propondo estratégias relacionadas ao programa de manejo do fogo (Prada & Marinho-Filho, 2004). Segundo Melo (2007), ainda são comuns as queimadas realizadas pelos Xavantes em atividades de caça com fogo.…”
Section: Resultados E Discussõesunclassified